THE EVOLUTION OF NOTION OF ECOLOGICAL COMPATIBILITY OF ECONOMIC ACTIVITIES IN AGRICULTURAL PRODUCTION - Мінькова, О. Г. (Scientific Progress & Innovations, 2015)
In the article the basic preconditions of origin of ecological farms have been defined, directions of ecological orientation in agricultural production have been generalized. Stages of formation of notion of ecological compatibility of economic activities in national and foreign theory and practice have been analyzed. There was reviewed the literature of their essence and the scientific and theoretical trend of development. The approaches to the classification of agro-ecological production models and their differences have been showed. The existing alternative methods of agricultural activity have been considered.